(untitled) (Revista de Crítica Literaria Latinoamericana, 2014)
This analysis of Claudia Llosa’s films (Madeinusa and Milk of Sorrow) begins by observing the great importance that she gives to the acoustic: language, voice, music, etc. It therefore investigates the relation between sound and image in her work, and the problematic of the process of naming, to show the tensions between these two levels. Ultimately, the argument is that Llosa points us to the possibilities as well as the pitfalls opened up by displacement and heterogeneity, by a scission between the senses. So, in contrast to any reading in terms of hegemony and/or counter-hegemony, the paper suggests that these are posthegemonic films. They refuse the indigenist dream of reconciling the country (indigenous with mestizo, highland with coast) in favor of a strategy of inhabiting and renaming the desert of the real.